The Role of Cardiac Computed Tomography in Tetralogy of Fallot and Pulmonary Atresia - Oktavia Lilyasari (The Indonesian Heart Association, 2015)
Congenital heart disease (CHD) occurs in about 6 to 8 of 1000 live births with the increasing prevalence can be attributed to major improvements in diagnosis and treatment. Imaging has an important role in diagnosis of CHD. It outlines anatomy and physiology, helps to refine management, evaluates the consequences of interventions and helps guide prognosis. However, no single available imaging modality fulfills these roles for all patients and diseases. Therefore, assessment for CHD must involve multimodalities that can be used in a complementary fashion, and that together are sensitive, accurate, reproducible, and cost effective, whilst minimizing harm.In previous years, the diagnosis and the treatment of congenital malformations have often depended on cardiac catheterization. In many institutions, cardiac catheterization still remains the gold standard against which other modalities are measured. In the past decade, however, imaging methodologies have increasingly shifted toward the use of less invasive and noninvasive techniques. Although echocardiography is the most commonly used imaging modality for diagnosis and follow-up of subjects with CHD, the evolution of cardiovascular magnetic resonance (MR) imaging and increasingly computed tomography (CT) does offer new ways to visualize the heart and the great vessels.